Випадковість та недостовірність як фактори військової політики - Гармаш, Д. (ХНУРЕ, 2021)
The article considers the issues of resolving military conflicts. It has been shown that the most extreme form of coercion in world politics is military violence. In today's world, the role of military force in resolving conflicts between states cannot be underestimated. Based on the history of many wars, it is safe to say that the use of this type of violence is associated with a number of surprises and uncertainties that can dramatically change the course of military conflict. Therefore, it is very important to study this aspect for the successful construction of a military strategy.
Keywords: філософія; фактори військової політики